Mechanoresponsive, Luminescent Polymer Blends Based on an Excimer‐Forming Telechelic Macromolecule. Issue 1 (12th November 2018) - Calvino, Céline; Sagara, Yoshimitsu; Buclin, Véronique; Haehnel, Alexander P.; del Prado, Anselmo; Aeby, Christian; Simon, Yoan C.; Schrettl, Stephen; Weder, Christoph
Abstract: A well‐known approach toward mechanochromic polymers relies on the incorporation of excimer‐forming fluorophores into a matrix polymer and the disruption of aggregated chromophores when such materials undergo macroscopic mechanical deformation. However, the required aggregates and stress‐transfer processes have so far only been realized with select dye/polymer combinations. As demonstrated here, the utility of this approach can be extended by tethering an excimer‐forming cyano‐substituted oligo( p ‐phenylene vinylene) fluorophore to the two ends of a telechelic poly(ethylene‐ co ‐butylene) and blending small amounts (0.1–2 wt%) of the resulting aggregachromic macromolecule into polymer matrices such as poly(ε‐caprolactone), poly(isoprene), or poly(styrene‐ b ‐butadiene‐ b ‐styrene). All blends display mechanofluorochromic responses, and the ratio between the monomer and excimer emission intensities can be used to correlate the luminescence signal to the extent of deformation and to follow subsequent relaxation processes. The developed approach significantly expands the scope of blend‐based mechanoresponsive luminescent materials. Abstract : The use of a telechelic aggregachromic macromolecule allows different types of polymer matrices to display mechanochromic responsive behavior. The stress‐transfer from the matrix to the dye aggregates is found to be significantly improved so that an elastic deformation is reversibly translated into a fluorescence color change, significantly expanding the utility of blend‐based mechanochromic materials.